Atmospheric bubbling fluidized bed combustion: Application to high ash coals and approach to scientific research - Milioli, Fernando Eduardo (My University, 1996)
This work is concerned with research on atmospheric bubbling fluidized bed combustion (AFBC) applied to mineral coals of high ash content. Coals is considered in a scenario of power generation both domestic and world-wide, and native high ash coal is placed as a solution for energy production in Brazil. As compared to conventional coal firing techniques, fluidized bed combustion arises as the most appropriate process for burning Brazilian coals. The main problems associated with high ash coal burning are well controlled by applying the technique. A review is performed on the state of the art on AFBC applied to high ash coals. It is seen that for both Brazilian and world-wide research, technological development overcomes by far scientific research. The need for scientific research is addressed An evaluation of mathematical modeling on AFBC is performed. The basic theories and usual approaches are considered, and the comprehensive modeling conception is evaluated as for its scientific relevance. Modeling proposals are advanced, and empirical requirements are pointed out on a modeling validation point of view.
Keywords: Fluidized Bed Combustion; High Ash Coals; Mathematical Modeling